Artesunate may inhibit liver fibrosis via the FAK/Akt/β-catenin pathway in LX-2 cells - Jian Lv; Ruidan Bai; Li Wang; Jiefang Gao; Hong Zhang (BMC, 2018)
Abstract Background An increasing number of studies are investigating the effects of Chinese medicine on hepatic fibrosis, but only few studies have examined the anti-fibrogenic properties of Artesunate (ART). The aim of the present study was to explore the anti-fibrotic effects of ART on LX-2 cells, the human HSC cell line, and to determine potential molecular mechanisms via the focal adhesion kinase (FAK)/ protein kinase B (Akt)/ β-catenin pathway. Methods LX-2 cells were stimulated with different concentration of ART (0, 12.5, 25 and 50 μg/ml) for 12, 24, 48 or 72 h, their proliferation was analyzed using the Cell Counting Kit-8 (CCK-8) assay. LX-2 cells were treated with different doses of ART (0, 12.5, 25 and 50 μg/ml) for 24 h, their apoptosis was measured using flow cytometry, the levels of mRNAs encoding collagen I or α-smooth muscle actin (α-SMA) were determined using reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and the levels of key proteins in the FAK/Akt/β-catenin signaling pathway were assessed by western blotting. Specific inhibitors of FAK were added to the LX-2 cells cultures to explore the potential signaling. Results Exposing LX-2 cells to ART efficiently inhibited their proliferation, significantly promoted early apoptosis in a dose-dependent manner, and markedly downregulated the mRNA expression of α-SMA and collagen I. In addition, ART, similar to FAK inhibitor PF562271 significantly inhibited the FAK/Akt/β-catenin signaling pathway by reducing the levels of phosphorylated FAK, Akt and GSK-3β. Conclusions Our present study shows that ART could regulate the proliferation, apoptosis and activation of LX-2. Meanwhile, the anti-fibrogenic mechanisms of ART was correlated with FAK/Akt/β-catenin pathway. Future research should verify and extend these findings, as well as explore other molecules and therefore serve as useful therapeutic targets.